AGAMA DAN FILSAFAT PERENNIAL PERSPEKTIF SEYYED HOSSEIN NASR - Abu Syahrin (UIN Sumatera Utara, 2019)
Perennial Philosophy (Philosophy Perennis) is the most monumental work of Seyyed Hossein Nasr's thought, and with that thought he succeeded in bringing together the religion of Islam, philosophy and Science which he said would remain forever. As a universal religion Islam is a continuation of the religions that have been revealed to the apostles, starting Adam a.s. arrived at the Prophet Muhammad. the whole religion is called al-Islam, which in essence is a total surrender to God.Even so according to Nasr, even though Islam and western religions and traditions have equality in several respects, Muslims must not take Western values and views for granted. There must be cech and balance, there must be criticism and auto criticism regarding Western ontology, especially dealing with modern science. The importance of criticizing the basis of modern science ontology, according to Nasr, is because ontology is the most fundamental part of the development of science.Keyword : Religion, Philosophy Perennis, and Seyyed Hossein Nasr